MULTIMODAL FEEDBACK PROVISION IN IMPROVING PRE-SERVICE TEACHERS’ COMPETENCE - Fazri Nur Yusuf; Utami Widiati; Teguh Sulistyo (Indonesian Journal of Applied Linguistics, 2017)
Studies on potentials of feedback over English language teaching seem to have not been well-revealed, including studies on the use of feedback to improve English pre-service teachers’ competence. The present study investigates to what extent a multimodal feedback can influence pre-service teachers’ teaching, and which teaching aspects are influenced. Twenty five pre-service teachers taking Microteaching Course served as respondents supervised by a course advisor. The data were collected by teacher observation in a rating-scale form, self-appraisal, and interviews. The data were analyzed by using correlated sample t-test and the eight teaching components proposed by Brown (2001). The results showed that after multimodal feedback provision, pre-service teachers indicated an improvement significantly in seven out of eight teaching aspects. The provision of multimodal feedback could improve their teaching competence on preparation, instructional objective elicitation, mastery of instructional materials, use of media, and classroom management, including classroom language. But, the results do not indicate that they perform well on reflection and follow-up due to some reasons. In addition, the results evince that multimodal feedback provision could improve pre-service teachers’ pedagogical competence when the multimodal feedback is integrated with content, interpersonal relationship, and management.